2017
DOI: 10.1016/j.jallcom.2017.02.082
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial properties of Cu/Ni/Mg2Si joints prepared in one step by the spark plasma sintering method

Abstract: Cu/Ni/Mg 2 Si thermoelectric bonded joints were prepared in one step by the spark plasma sintering (SPS) method using Mg and Si powders to form Mg 2 Si. The microstructure and elemental distribution across the interfaces were determined, and the formation of new phases at the interface was investigated and related to joint properties, including shear strength and contact resistance. Joint formation was accompanied by the formation of two ternary Mg-Si-Ni layers, an η-layer with Ni 2 Si as a precipitate next to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
(11 reference statements)
0
13
0
1
Order By: Relevance
“…For example, n-type Mg 2 Si 0.3 Ge 0.05 Sn 0.65 boasts a zT at ~750 K of 1.4 while p-type Mg 2 Ge 0.4 Sn 0.6 only reaches a maximum zT of 0.5 at around the same temperature. Despite the low efficiency of p-type Mg-based thermoelectric materials, some preliminary results on device design and construction of devices based on these materials has already been achieved 15,16,58,[121][122][123][124] . The low performance of the ptype Mg-based thermoelectric materials creates serious limitations on the construction of devices, and most reports on the use of these materials in modules are on n-type legs 15,58,121 .…”
Section: Applications and Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, n-type Mg 2 Si 0.3 Ge 0.05 Sn 0.65 boasts a zT at ~750 K of 1.4 while p-type Mg 2 Ge 0.4 Sn 0.6 only reaches a maximum zT of 0.5 at around the same temperature. Despite the low efficiency of p-type Mg-based thermoelectric materials, some preliminary results on device design and construction of devices based on these materials has already been achieved 15,16,58,[121][122][123][124] . The low performance of the ptype Mg-based thermoelectric materials creates serious limitations on the construction of devices, and most reports on the use of these materials in modules are on n-type legs 15,58,121 .…”
Section: Applications and Devicesmentioning
confidence: 99%
“…The total resistance of the electrodes, segmented legs, and respective bonding interfaces is reported to represent less than 2% (50 µΩcm 2 ) of the internal resistance of the materials used. Mg 2 Si is normally bonded to Ni 16,123,133 because at its working temperature, these materials are not expected to react 16,133 . Ni has been directly bonded by SPS to Sb-doped Mg 2 Si powder between two layers of Ni powder 133 , with its thermoelectric Figure 9.…”
Section: Electrode Bonding Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to previous studies, the Ni/Mg 2 Si combination was reported to have contact resistances lower than 10 μΩ·cm 2 [ 5 ]. Long-time isothermal annealing tests, such as annealing at 450 °C for 600 h [ 6 ] or at 550 °C for 168 h [ 7 ], also demonstrated good thermal stability. However, isothermal annealing test is not enough to confirm the reliability, and temperature cycling (TC) is more appropriate to examine the robustness of the Ni/Mg 2 Si interface for real situations.…”
Section: Introductionmentioning
confidence: 99%
“…Необходимо отметить этот положительный эффект для ТЭМ, имеющих концентрацию носителей, как правило, превышающую 10 19 см −3 .Для обеспечения омического контакта необходимо использовать материалы контактных слоев с низким удельным сопротивлением, например Mo, W, Co и Ni[23]. Для низких температур хорошо зарекомендовал себя Ni, получаемый вакуумным напылением[19,27,28,39]. Проведенные исследования методом ОЭС образцов с контактами из Ni толщиной 400−500 нм после термической обработки в вакууме при 577 K показали, что при этой температуре Ni перестает выполнять функции барьерного слоя[23,27].…”
unclassified